Zenon Fajfer’s Theory of Liberature - Urban, Justyna (Pitannâ lìteraturoznavstva, 2013)
The main purpose of this article is presentation and critical analysis of Zenon Fajfer’s notion “liberatura “liberture”” (developed also by Katarzyna Bazarnik). The conception of liberature as “total literature in which the text and the space of a book constitute an inseparable whole” is known since1999 inPolish Literary studies and now is a wide discussed subject abroad. Being a new idea, after all, it concerns also very old (existing from the beginnigs of letters and literature, for example: visual poems of Simmias of Rhodes (of 325 BC) and Theocritus (of III BC)) fenomena. The conception of liberature was invented for the sake of the Oka-leczenie [‘Eyes-ore’], the first book created by Fajfer and Bazarnik (since 1988 until 2009) and described by them as very sample of 'liberature'. Authors just don't "made" another example of art book or book-art, but literary work of art including sphere of iterests and meaning with “phisical elements”, “bookish elements” or “editorial formality”. Flank of transfer from meanings of used words here subsequent and very important was (away from conventions) semantically carrying manner of book edition as the way performing. Term „liberature” Fajfer originates not only from Latin: “līběr, līběră, līběrǔm” = ‘liberty’, but also from “līběr, lībri” = ‘book’ and “lībră, lībrae” = ‘Libra’ (‘scales’). Freedom in “liberature” means liberation from rules and publishing conventions. It has to indicate capability to involving publishing form to construction of integrity of transfer to significant integrity of text with its unindifferent physical carrier “book”. Then it indicates necessity of selection of – weighing word “weight” also in respect visual, quantitative or respect letter composition, behavior of proportions between text, image, the way of pagination etc. The Fajfer’s concept, continuously obtained, inclines for assigning question, among others, about mutual rates of balks literature but liberature, liberature but visual arts, about place liberature in literature, about still actual definition of book.